Geographic patterns of electrophoretic and morphological variation in the sagebrush least chipmunk (Tamias minimus scrutator) - Bell, Kayce C.; Baccus, Ramone (THERYA, 2022)
Variation and differentiation among populations provide a framework to decipher how populations are, or are not, changing due to gene flow, genetic drift, and selection. The sagebrush least chipmunk (Tamias minimus scrutator) is distributed in arid and semi-arid habitats throughout much of the Great Basin and adjacent regions. The broad distribution and variation in elevation of populations make this a good system to assess population variation and the forces shaping differentiation. Here, we use allozyme and morphological datasets to: 1) assess the relative roles of geographic locality and elevation of populations in shaping population structure; 2) examine the level of differentiation of peripheral and isolated populations; and 3) compare the genetic and morphological signals of population variation and structure. We sampled 312 individuals from 12 T. minimus scrutator populations and other areas of their distribution. Individuals were measured for 27 genetic and 61 morphological traits. These datasets were analyzed to determine the distribution of variation and the differentiation among populations and tested for correlations with geographic distance and elevation. Multiple approaches were used to thoroughly compare the signals from each dataset. We found 13 polymorphic electrophoretic loci with most of the variation structured among populations within regions. Eight loci exhibited elevational heterogeneity but most high-elevation populations showed no heterogeneity among populations. Thirty-two morphological characters varied among populations but with no discernable trends across regions or elevations. Populations had varying levels of asymmetric distinctness in morphological characters, but there were no significant differences among populations. Morphological and genetic distance measures were correlated and there was some evidence of a correlation of genetic and geographic distance. We also found some correlation of asymmetric distances with morphological or genetic distances at smaller scales. There was substantial variation of genetic and morphological traits among sagebrush least chipmunk populations. Each population had a unique genetic signature and significant morphological differentiation. Our results suggest that genetic drift is contributing to the structure of these populations, with some evidence of selection shaping the distribution of variation at different elevations. The peripheral populations had mixed signals of isolation among the different datasets, with an overall signature suggesting that genetic drift is also driving the variation among these populations. The different measures of population variation yielded inconsistent signals of population structure, highlighting the need for multiple approaches to assess population variation. The variation among sagebrush least chipmunk populations is impacted by a variety of factors and contemporary investigations may reveal populations responding to alterations in habitat and climate.